The political and social thoughts of Satı Bey : exporing the ideology of an Ottoman patriot - Zengin, Ertuğrul. (Thesis (M.A.) - Bogazici University. Atatürk Institute for Modern Turkish History, 2010., 2010)
This thesis scrutinizes the political and social thoughts of an Ottoman intellectual Satı Bey who defended Ottomanism as a remedy to the problems of the collapsing Empire. Satı Bey besides being a successful bureaucrat was also an influential thinker who revised the old ideology of Ottomanism by placing the “individual” as the center of his thought. He synthesized the Young Turk ideology which prioritized a modernization program guided by the notions of “science” and “progress” with the Young Ottoman theme of vatan as the basis of the allegiances of the citizens to the state. He attached great importance to primary education to nurture “a new individual,” who as a loyal citizen of Ottoman Empire would be the bearer of modern thinking. Satı lived in an age of social and political turmoil when different agendas were formulated by the different ideological camps. As a committed Westernist and Ottomanist, he clashed with the leading intellectuals of his period, like the Turkish nationalist Ziya Gökalp, the thinker and educationist İsmail Hakkı Baltacıoğlu and the Minister of Education of his period, Emrullah Efendi. Especially his discussions with Ziya Gökalp are revealing to observe the similarities and differences, converging and diverging points of Turkish nationalism and Ottoman patriotism of his period. Satı’s discussion with Ziya Gökalp on the objective of education was transformed into a broad-based discussion of the existence of national consciousness as an entity. Satı objected the existence of any transcendental entity above the realm of individual. He rested on the will of the individual independent from the all external forces or ideological construction. However, Satı also recognized the shortcomings of such an individualistic formulation of Ottomanism while the Empire was confronting the danger of the dissolution in the ethnic lines. He was aware of the necessity to accommodate to his individualist and materialist ideology an idealist construction which would serve as a source of loyalty to Ottoman state. At this point he broke with the leading Westernist Young Turk intellectuals of Prince Sabahaddin and Abdullah Cevdet who regarded federalism a practical option for the state against dissolution. Although he criticized explicitly Committee of Union and Progress after the departure of the leading cadre of the Committee for conducting harsh centralization policies, he never declared an open support for federalism as a solution. To the contrary, he sought for a new loyalty which would not instigate any ethnic or religious cleavages, but at the same time would provide the ground of legitimacy for the state. Thus he utilized and revised the Young Ottoman notion of vatan for the end of offering an inclusive ground for the people of Ottomans as an alternative to the exclusionist project of nationalism. Based on this analysis, the thesis argues that Ottomanism, which was perceived as a state policy after the Gülhane Receipt, and was theorized by an Ottoman intellectual Satı Bey in the Second Constitutional period remained a vital political alternative at least intellectually just before the dissolution of the Empire.
Keywords: Education -- Turkey -- History -- 20th century.